The effect of iron (Iii) co-insertion in magnesium-aluminum hydrotalcites obtained by precipitation method at ph 11 - de Sá, Igor Silva; Kawahara, Creuza Kimito Caceres; Barbosa, Graciele Vieira; de Souza, Eliane Ferreira; Ramos, Talita Cuenca Pina Moreira; Amoresi, Rafael Aparecido Ciola [UNESP]; da Silva, Margarete Soares; Cavalheiro, Alberto Adriano (Trans Tech Publications, 2018)
Hydrotalcite are anionic clay material presenting LDH arrangement and high porosity and specific areas, which make it a good adsorbent for pollutant species in water. Besides that, that material type can be used as catalyst or catalyst support in several industrial processes. The most common compositions is based on metallic mix hydroxide with high content of magnesium, but their adsorptive properties arise from aluminum replacement in layer structure. The present work presents the synthesis of carbonated magnesium-aluminum hydrotalcite through the precipitation method in order to investigate the co-insertion of iron (III) in aluminum site. It was found the iron (III) co-inserted samples obtained at 100 and 200 ºC for 4 hours present no substantial harming in relation to the common magnesium-aluminum composition. All of the samples presented high porosity and specific area, becoming an alternative anionic adsorptive.
Keywords: Hydrotalcite; Hydroxide Precipitation; Iron III; Phase formation; Porosity